The Impact of Prenatal Yoga on Pregnancy Outcomes and Maternal Psychological Well-Being: A Systematic Review and Meta-Analysis - Muhammad Sobri Maulana; Dwitia Pratiwi; Arditya Prayogi (JURNAL IBU DAN ANAK, 2026)
Prenatal yoga integrates physical postures, breathing, relaxation, and mindfulness. It is increasingly recommended as a low-intensity adjunct to routine antenatal care, yet estimates of its effects on pregnancy outcomes and maternal psychological well-being vary across trials and reviews. This article aim to synthesize evidence on whether prenatal yoga improves maternal psychological outcomes, including stress, anxiety and depression, and pregnancy or birth outcomes, including labor duration, vaginal birth, cesarean section, perineal trauma, and preterm birth. A systematic review and meta-analysis framework was developed according to PRISMA 2020. The planned databases were PubMed/MEDLINE, Embase, Cochrane CENTRAL, ProQuest, and Scopus from inception to 9 May 2026. Eligible studies were randomized or controlled trials enrolling pregnant women and comparing prenatal yoga with usual antenatal care, education, other exercise, or non-yoga controls. Risk of bias was appraised using the Cochrane RoB 2 domains, and certainty was summarized with GRADE. Random-effects synthesis was prioritized because intervention content and outcomes varied. For result, the core evidence map was anchored in a broad review of 31 studies including 2,413 pregnant women, of which 29 studies with 2,217 participants contributed to meta-analysis. Prenatal yoga was associated with lower perceived stress (SMD -1.03, 95% CI -1.55 to -0.52), anxiety (SMD -0.91, 95% CI -1.49 to -0.33), and depression (SMD -0.47, 95% CI -0.90 to -0.04). It was also associated with shorter labor duration (MD -117.75 minutes, 95% CI -153.80 to -81.71) and increased odds of normal vaginal birth (OR 2.58, 95% CI 1.46 to 4.56). A newer RCT-only synthesis in nulliparous women reported lower cesarean section (RR 0.45, 95% CI 0.38 to 0.54), preterm birth (RR 0.29, 95% CI 0.15 to 0.56), and second-degree perineal laceration (RR 0.41, 95% CI 0.25 to 0.69). Prenatal yoga appears to improve psychological well-being and several birth outcomes. Confidence is limited by heterogeneity, incomplete reporting of randomization and allocation concealment, unavoidable lack of participant blinding, small trials, and variable intervention fidelity. Well-powered multicenter RCTs using standardized yoga protocols and harmonized outcome measures are needed.